Environmental Education in a reflexive perspective in Young and Adult Education (Research, Society and Development, 2020)
This work aims to bring reflections on the understanding of Environmental Education (EE) that is offered in “Educação de Jovens e Adultos (EJA)” program. Through bibliographic studies, we seek to comprehend concepts and questions involved in EE and analyze present conceptions in documents that guide EJA’s curriculum. The article brings a brief timeline about Environmental Education in Brazil in order to comprehend the change of conception through the years, as well as reflections in the educational context, especially in EJA. Analyzes, also, the concept of sustainability and how the educational practices can contribute to effectuate it’s realization.